ANALYSIS OF THE AVIATION INDUSTRY IN INDONESIA PERIOD 2003-2015 BASED ON DOMESTIC PASSENGER GROWTH AND THE STRATEGIC IMPLICATION FOR AIRLINES AND GOVERNMENT - Sutan Banuara; John Tampil Purba (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2017)
The objective of the study was to analyze the growth of the number of domestic passengers in Indonesia based on emprical data of the last 12 years to forecast the number of domestic passenger for 2016-2021 by using panel data modeling with random effects model technique. The research using independent variable air traffic, ticket prices and per capita income has never been done in the Indonesia’s aviation industry, but research with the same model ever done in the industry of electrical household. The results of the study are useful for strategic planning for companies in developing the market and government of Republic of Indonesia to determine the right public policies needed to support the aviation industry development which able to accelerate economic growth, ensure the safety and convenient of air transport passengers and the sustainability of aviation industry. The results of this study indicate that the variable number of air traffic can be explained by ninety one point eleven percent by variable number of air traffic, yield and per capita income and has a close relationship to the number of domestic passengers in Indonesia.